Rainbow valley eaudiobook - Montgomery, L.M (Anne of Green Gables, 2014)
Anne Shirley is all grown up and married to her longtime sweetheart Gilbert Blythe. What's more, they have six wonderfully mischievous children—who've just discovered a new secret hideout. When the Blythe boys and girls learn that an eccentric family has moved into a nearby mansion, they are bubbling over with curiosity. The new family is the Merediths, and they have two boys and two girls of their own. They also shelter a runaway named Mary Vance, but sadly she's about to be sent away to an orphanage. Can the Blythe children find a way to help? Listeners will delight as the frolicsome bands of children team-up on a goodhearted adventure to save the day! L.M. Montgomery's Anne of Green Gables novels are enduring classics that the whole family can cherish. First published in 1919, Rainbow Valley continues the captivating saga begun in the books Anne of Green Gables, Anne of Avonlea, and Anne of the Island.